Analysis of Students’ Spiritual Humanism through Seyyed Hossein Nasr's Thoughts and Its Implications for Islamic Learning - Adiningsih, Regita Pramesti; Muthohirin, Nafik; Humaidi, Mohammad Nurul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Seyyed Hossein Nasr is a 20th-century Muslim thinker who succeeded in linking the spiritual and rational dimensions of modern life. His thinking responds to various problems of modernity experienced by contemporary humans. This article wants to look further into the problem of modernity on the social and spiritual behavior of students and its implications for the practice of Islamic education in Islamic religious universities in Indonesia through Nasr's thoughts. This article is important because it wants to reveal the various problems of modernity that can lead students to behave negatively. Students behave far from social and religious norms, such as drinking alcohol, dirty talk, promiscuity, and various other social deviations, but are often considered normal. This ultimately has an impact on attitudes that tend to neglect their responsibilities as students, decrease motivation to study, and many even do not continue their studies. As an indication, they are experiencing a spiritual crisis. This research uses a descriptive qualitative research method with an analytical study approach that prioritizes the depth of argumentation and verification of literature references and evidence in the field. Data mining was also carried out through in-depth observations and interviews with 110 students taken from all study programs at the Universitas Muhammadiyah Malang. The research found that the modern crisis causes students' spiritual piety to experience degradation due to deviant social behavior habits and disregard for religious norms. In the aspect of implementing Islamic learning, it is necessary to evaluate strengthening humanist and spiritual values at the university level, as well as realizing the integration of spiritual values in the education curriculum.